Формування конкурентної стратегії підприємств - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia (My University, 2019)
UK: В статті розглянуто особливості формування конкурентної стратегії підприємства. Доведено, що стратегія задає певні рамки, які дозволяють виявити і оцінити трансформаційні умови внутрішнього середовища розвитку підприємства як системи і зумовленими в цьому аспекті змінами потреби в ресурсному забезпечені господарського процесу. Обгрунтовано, що конкурентні переваги за сукупністю ресурсно-вартісних можливостей підприємства у функціональних сферах його діяльності та ефективного управління забезпечують підвищення конкурентоспроможності продукції. Аналітичний інструментарій конкурентної стратегії у комплексній взаємодії формує механізм, який сприяє досягненню конкурентних переваг підприємства на ринку, з урахуванням чинників внутрішнього та зовнішнього середовища. Розроблено комплекс напрямів і заходів конкурентної стратегії щодо ефективного організаційно-економічного середовища ресурсно-інноваційного забезпечення підприємства. EN: Features of formation of the competitive strategy of the enterprise are substantiated; conceptual positions of this process are defined. It is proved that the strategy sets certain frameworks that allow identifying and evaluating the transformational conditions of the internal environment of enterprise development as a system and changes in the need for resource provided economic process caused in this aspect. It is substantiated that the competitive advantages in the aggregate of resource and value opportunities of the enterprise in the functional areas of its activity and effective management allow increasing the competitiveness of products. The analytical toolkit of competitive strategy in a complex interaction forms a mechanism that sets the vector of action for managing the competitiveness of the enterprise in the market and contributes to the achievement of competitive advantages taking into account the factors of the internal and external environment. The formation of a competitive strategy is systemic in nature, that is, all elements of the mechanism are interconnected and purposefully function to achieve the goal, namely ensuring the competitiveness of the enterprise. It is justified that an enterprise rarely comes up with one strategy, so specific criteria for the weight of competitive advantages are needed to identify and analyze other strategies by a set of criteria. Economic growth, increasing production and especially the dynamic growth of additional income is no longer possible without quality resource (land) and innovations, advanced technologies that are available only today to big business, and which owns large tracts of land and uses capital from other industries. A set of directions and measures of a competitive strategy for an effective organizational and economic environment of providing resource and innovation support has been developed
Keywords: конкурентна стратегія; конкурентні переваги; стратегія; конкурентоспроможність; підприємство; конкуренція; competitive strategy; competitive advantages; strategy; competitiveness; enterprise; competition